Post-Covid-19 Pandemic Economic Recovery: Optimizing the SDG's Program Through Local UMKM - Fahmi Ihsan Margolang; Lia Nurhasanah (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
The Covid-19 pandemic has become quite a serious problem, leaving all countries in the world in ruins, almost all development sectors are in disarray, especially in the economic sector. This research aims to combine and optimize the SDG's Program with Local MSMEs as an effort to recover the post-Covid pandemic economy -19. This research method uses a literature study, by analyzing the SDG's programs which have a correlation with the economy, which is then linked to empowering local MSMEs. The results of this research show that the Sustainable Development Goals are still not optimal due to not being on target between planning and budget use, this is what causes slow economic growth, especially in MSMEs, therefore it is necessary to increase awareness to optimize the SDG's Program in an effort to increase and empower Local MSMEs as an effort Indonesia's economic recovery.